Current Research and Future Trends in Solar Energy Technology Integration with Smart Grids - ADEPOJU, Enoch; LAWAL, Olatunji Ahmed (ABUAD Journal of Engineering and Applied Sciences, 2025)
The growing challenges of solar intermittency and grid instability threaten the reliability and scalability of renewable energy integration worldwide. This study addresses these critical issues by evaluating recent advances in photovoltaic (PV) systems, concentrated solar power (CSP), energy storage, and adaptive grid controls. Through analysis of global case studies, such as Vietnam’s solar farms and South Africa’s AI-enabled microgrids, it demonstrates how smart inverters, AI algorithms, and hybrid systems effectively reduce variability and enhance overall efficiency. Reviewed literature highlights AI solar forecasting technologies achieving up to 95% accuracy, while hybrid PV-CSP-storage systems deliver 25% higher efficiency. Building on these insights, the study proposes a scalable roadmap for renewable energy adoption that prioritises technological synergy and policy innovation, thereby accelerating the global transition toward sustainable, resilient energy systems.